2020
DOI: 10.1111/coa.13562
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis predictors for neck sublevel IIb in papillary thyroid carcinoma

Abstract: Objective To investigate possible metastasis predictors for neck sublevel IIb in papillary thyroid carcinoma (PTC) with lateral neck metastasis and to determine the reliability of preoperative ultrasound‐guided fine‐needle aspiration biopsy (FNAB) as a method of detecting positive lymph nodes in sublevel IIa in comparison with the finding of definitive pathohistological analysis. Design Prospective study with patients with proven lateral neck metastases from PTC at the time of initial diagnosis. All patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Previous studies have investigated some predictors of positive micrometastasis in central lymph nodes in patients with papillary thyroid cancer (20)(21)(22)(23)(24)(25)(26)(27). In the study of Seong et al, in line with the present study, they found that a distance of less than 1.9 mm was a significant correlation as a predictor of central lymph node metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have investigated some predictors of positive micrometastasis in central lymph nodes in patients with papillary thyroid cancer (20)(21)(22)(23)(24)(25)(26)(27). In the study of Seong et al, in line with the present study, they found that a distance of less than 1.9 mm was a significant correlation as a predictor of central lymph node metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…Among the various studied factors, exposure to ionizing radiation of the head and neck region in childhood is a well-established TC risk factor ( 5 , 20 , 21 ), but increased exposure to radiation in general might also contribute ( 4 ). Many studies, summarized and reviewed in this article, have focused on other possible risk factors, such as chromosomal and genetic alterations, iodine intake, TSH level, autoimmune thyroid disease, gender, estrogen, obesity, lifestyle changes, and environmental pollutants ( 52 - 54 ). The results are currently inconclusive, sometimes even controversial, and there is a possibility that yet undiscovered carcinogens, especially during intrauterine life or early childhood, might be responsible for increased TC incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Patient with N0 should be treated only for central region lymph node dissection, and full neck lymph node dissection should be performed when a lateral cervical lymph node is present preoperatively or appears during postoperative follow-up. ( 6 , 17 )…”
Section: Discussionmentioning
confidence: 99%